Optimization of Commercially Off the Shelf (COTS) Electric Propulsion System for Low Speed Fuel Cell UAV - Zulkifli, Muhammad (2013)
A Master of Science thesis in Mechatronics Engineering by Muhammad Zulkifli entitled, "Optimization of Commercially Off the Shelf (COTS) Electric Propulsion System for Low Speed Fuel Cell UAV," submitted in March 2013. Thesis advisor is Dr. Mohammad Amin Al Jarrah. Available are both soft and hard copies of the thesis.